Silicone-polyether copolymers for use in bubble control formulations
By synthesizing organosilicon-polyether copolymer (SPE copolymer) as a foam control agent, the problems of the dosage and transparency of foam control agents in detergents in the prior art have been solved, achieving efficient foam control without affecting the transparency of detergents.
Patent Information
- Application Number
- CN202480043129.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-06
- Filing Date
- 2024-06-12
- Publication Date
- 2026-01-23
AI Technical Summary
Existing silicone foam control agents are difficult to maintain at low addition levels in detergent compositions while simultaneously achieving high foam control, and they also affect the transparency of the detergent.
An SPE copolymer suitable for foam control agents was prepared by synthesizing an organosilicon-polyether copolymer (SPE copolymer) through a hydrosilylation reaction, controlling the reaction conditions and the ratio of starting materials.
It provides effective foam control while maintaining detergent transparency at low addition levels, and is suitable for applications such as water-based coating systems, printing inks, and liquid laundry detergents.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_13
Abstract
Description
Cross Reference to Related Applications
[0001] This application claims the benefit under 35 U.S.C. §119(e) of U.S. Provisional Patent Application Serial No. 63 / 525,183, filed July 6, 2023. U.S. Provisional Patent Application Serial No. 63 / 525,183 is hereby incorporated by reference. TECHNICAL FIELD
[0002] The present invention relates to a silicone-polyether copolymer and methods of making and using the same. The copolymer can be used in foam control applications. BACKGROUND
[0003] Silicone foam control formulations are known for use in a variety of applications such as pulp and paper, chemicals, textiles (e.g., dyeing and / or laundry), fermentation and sugar beet processing, water treatment and metal working, as well as in paints, latex, cement, fertilizers, soaps, and detergents. Such foam control formulations generally include a variety of ingredients, including a silicone “foam control agent,” which can also be referred to as an antifoam agent, defoamer, foam suppressant, or foam inhibitor. Foam control agents are materials that, when added at low concentrations, reduce or control the amount of foam in a liquid that would otherwise foam. Polyorganosiloxanes, and more particularly, polydimethylsiloxanes (PDMSs), are the most common foam control agents. Silicone foam control compositions also typically include a hydrophobic inorganic filler (e.g., silica and / or zeolite) and a surfactant, which, when the formulation is provided as an emulsion, facilitates the dispersion of the formulation and provides stability.
[0004] U.S. Patent 6,521,586 discloses silicone-based foam control agents, particularly for use in aqueous compositions, preferably detergent compositions. The detergent industry is constantly evolving, with a trend towards using detergent compositions that will perform with higher efficiency than hitherto, due to environmental concerns, energy saving efforts, changes in machine design, water saving and changes in laundry habits. There is a need to control foam from, for example, increased surfactant levels in detergent compositions, the use of surfactants with a higher foam profile than traditional surfactants, changes in laundry conditions. Since silicone foam control agents do not directly contribute to the cleaning ability of a detergent composition, it is desirable to keep the level of such foam control agents at a minimum. Therefore, there is a need to develop improved foam control agents for incorporation into detergent compositions. There is also a need for foam control agents that can be used in clear liquid laundry detergents, such that the foam control agent does not affect or only minimally affects the clarity of the detergent. SUMMARY
[0005] A silicone-polyether copolymer (SPE copolymer) is provided. A method for synthesizing the SPE copolymer is also provided. The SPE copolymer can be used as a foam control agent. DETAILED DESCRIPTION
[0006] The method for synthesizing the SPE copolymer described above comprises: 1) combining starting materials comprising A) an alkenyloxy-terminated, aryl-terminated glycol ether, B) a polyorganohydrogensiloxane, and C) a hydrosilylation reaction catalyst under conditions to effect a hydrosilylation reaction. The starting materials can optionally further comprise D) an alkenyl-functional aromatic compound different from A) the alkenyloxy-terminated, aryl-terminated glycol ether, E) a dienyl-terminated siloxane oligomer, F) a solvent, or a combination of two or more of D), E), and F).
[0007] Step 1) can be conducted in any convenient equipment by any convenient means. For example, when the method is conducted in a batch mode, a reactor having heating and cooling provisions, such as a jacket containing water or other heat transfer fluid, and mixing provisions, such as baffles and / or agitators, can be used. One or more of the starting materials can be combined in the reactor, and then the remaining starting materials can be added all at once, or continuously or intermittently in aliquots to the reactor. For example, the starting materials having alkenyl groups, such as A) the alkenyloxy-terminated, aryl-terminated glycol ether, and when used, D) the alkenyl-functional aromatic compound and / or E) the dienyl-terminated siloxane oligomer, can be combined with B) the polyorganohydrogensiloxane, and then all or a portion of C) the hydrosilylation reaction catalyst can be added. Additional portions of the alkenyl-functional starting materials and C) the hydrosilylation reaction catalyst can be added one or more times until the silicon-bonded hydrogen atoms of B) the polyorganohydrogensiloxane have reacted with the alkenyl groups.
[0008] Alternatively, the starting materials having alkenyl groups, i.e., A) the alkenyloxy-terminated, aryl-terminated glycol ether, and when used, D) the alkenyl-functional aromatic compound and / or E) the dienyl-terminated siloxane oligomer, can be combined with all or a portion of C) the hydrosilylation reaction catalyst in the reactor. Then, B) the polyorganohydrogensiloxane can be added continuously or intermittently with heating or cooling to control the rate of reaction. Without wishing to be bound by theory, when the hydrosilylation reaction is conducted on a commercial scale, it can be desirable for safety reasons to separate B) the polyorganohydrogensiloxane and C) the hydrosilylation reaction catalyst until just prior to reaction with the alkenyl-functional starting materials.
[0009] The hydrosilylation reaction in Step 1) can be conducted at a temperature of from 50 °C to 150 °C for a time sufficient to react all of the silicon-bonded hydrogen atoms of starting material B) with the alkenyl groups of starting material A) (and when present, starting material D) and / or starting material E)).
[0010] The method can also optionally include one or more additional steps. For example, one or more of the starting materials can be optionally dissolved in F) solvent prior to or during step 1). For example, C) hydrosilylation catalyst can be dissolved in F) solvent prior to combining with other starting materials used in step 1). The method can optionally further include step 2) recovering the SPE copolymer. Recovery can be performed by any convenient means, such as one or more of the following:
[0011] decolorization (e.g., by batch-wise treatment of the reaction product comprising the SPE copolymer prepared in step 1) with an adsorbent such as activated carbon or by continuous treatment of the reaction product by passing it continuously through a packed bed of activated carbon);
[0012] filtration (e.g., to remove activated carbon and / or other particulates in a batch process); and / or
[0013] stripping and / or distillation (e.g., to remove solvent (when used), byproducts of the hydrosilylation reaction (if any, such as isomerization products), and / or unreacted starting materials, e.g., when starting materials are in excess, as described below, such as A) alkenyloxy-terminated, aryl-terminated glycol ether).
[0014] Starting material A) alkenyloxy-terminated, aryl-terminated glycol ether has the general formula A1): wherein X is H or methyl, D has the empirical formula -C2H4- or -C3H6-, and subscript n is 1, 2, or 3. Alternatively, X can be methyl. Alternatively, D can have a formula selected from -CH2-CH2- or -CH2-CH(CH3)-. Alternatively, subscript n can be 1 or 2; and alternatively, subscript n can be 1. Alternatively, when X is H, and D is -C2H4-, then subscript n can be 2 or 3. Alternatively, when each R 3 is H, A) alkenyloxy-terminated, aryl-terminated glycol ether can have the general formula A2): wherein X, D, and subscript n are as described and exemplified above. Examples of alkenyloxy-terminated, aryl-terminated glycol ethers are shown in Table A below.
[0015]
[0016] Alternatively, the alkenyloxy-terminated, aryl-terminated diol ether can be selected from the group consisting of: (2-(allyloxy)propoxy)benzene; (2-(2- (allyloxy)ethoxy)ethoxy)benzene; (2-(2-(allyloxy)propoxy)propoxy)benzene; (2- ((2-methylallyl)oxy)ethoxy)benzene; (2-((2-methylallyl)oxy)ethoxy)benzene; (2-(2- ((2-methylallyl)oxy)ethoxy)ethoxy)benzene; and (2-(2-((2-methylallyl)oxy)propoxy) propoxy)benzene. Alternatively, the alkenyloxy-terminated, aryl-terminated diol ether can be selected from the group consisting of: (2-(allyloxy)ethoxy)benzene; (2- (allyloxy)propoxy)benzene; (2-((2-methylallyl)oxy)ethoxy)benzene; and (2-((2- methylallyl)oxy)propoxy)benzene. Alternatively, the alkenyloxy-terminated, aryl- terminated diol ether can be selected from the group consisting of: (2-(allyloxy)propoxy) benzene; (2-((2-methylallyl)oxy)ethoxy)benzene; and (2-((2-methylallyl)oxy)propoxy) benzene.
[0017] The alkenyloxy-terminated, aryl-terminated diol ether can be prepared by a method comprising combining starting materials comprising an alkylene glycol aryl ether (such as an alkylene glycol phenyl ether), a catalyst (such as a halogenated organic ammonium), and a halogenated alkenyl (such as allyl chloride) under conditions to effect a reaction. An aqueous base, such as aqueous sodium hydroxide, can be added with mixing and optionally with heating. The resulting slurry can be separated using, for example, a separatory funnel. The organic phase can be further purified, for example, by washing with water, separation, and stripping and / or distillation with heating and optionally under reduced pressure, to recover the alkenyloxy-terminated, aryl-terminated diol ether. For example, (2-(allyloxy)ethoxy)benzene (2-allyloxyethyl phenyl ether) can be prepared as described in U.S. Patent 5,466,845, Example 2a), and the alkenyloxy-terminated, aryl-terminated diol ether can be prepared as described in the following examples or as described in U.S. Patent 5,466,845 by changing the appropriate starting materials.
[0018] The following starting materials for preparing A) alkenyloxy-terminated, aryl- terminated diol ethers are available from The Dow Chemical Company of Midland, Michigan, USA. Ethylene glycol phenyl ether having the formula C6H5-0-CH2-CH2-OH is available as DOWANOL® EPh diol ether. Propylene glycol phenyl ether having the formula C6H5-0-CH2-CH(CH3)-OH is available as DOWANOL® PPh diol ether. ™ EPh diol ether. Propylene glycol phenyl ether having the formula C6H5-0-CH2-CH(CH3)-OH is available as DOWANOL® PPh diol ether. ™PPh glycol ether. Diethylene glycol phenyl ether having the formula C6H5-0-CH2CH2-0-CH2CH2-OH is available as DOWANOL PPh ™ DiEPh glycol ether. Dipropylene glycol phenyl ether having the formula C6H5-0-CH2-CH(CH3)-0-CH2-CH(CH3)-OH is available as DOWANOL DiEPh ™ DiPPh glycol ether.
[0019] A) the amount of alkenyloxy-terminated, aryl-terminated glycol ether depends on various factors, including B) the silicon-bonded hydrogen content of the organohydrogensiloxane, and whether one or both of D) an alkenyl-functional aromatic compound or E) a di-alkenyl terminated siloxane oligomer is present. However, the amount of A) the alkenyloxy-terminated, aryl-terminated glycol ether is sufficient to provide at least one silicon-bonded group of the formula A1') per SPE copolymer molecule as described above. Alternatively, the amount of A) the alkenyloxy-terminated, aryl-terminated glycol ether can be sufficient to provide a molar ratio of alkenyloxy groups of the starting material (A) to silicon-bonded hydrogen atoms in the starting material (B) of > 0 / 1 to 1.15, alternatively 1.1 / 1 to 1.15 / 1. Alternatively, the amount of starting material A) can be sufficient to react all of the silicon-bonded hydrogen atoms in the starting material B) such that the SPE copolymer contains no unreacted silicon-bonded hydrogen atoms. Alternatively, when starting materials D) and E) are present, the combined amount of starting materials A), D), and E) can be sufficient to react all of the silicon-bonded hydrogen atoms in the starting material B) such that the SPE copolymer contains no unreacted silicon-bonded hydrogen atoms.
[0020] Starting material B) in the above process is a polyorganohydrogensiloxane comprising units of the formula (B1): 1 3SiO 1 / 2 ) a (R 1 2SiO 2 / 2 ) b (R 1 HSiO 2 / 2 ) c wherein the subscripts a, b, and c represent the average number of each unit in the formula and have values such that a < 2, 20 < b < 60; 20 < c < 60; and each R 1 is an alkyl group of 1 to 12 carbon atoms. Examples of alkyl groups of R 1 are methyl, ethyl, propyl (including n-propyl and isopropyl), butyl (including n-butyl, isobutyl, sec-butyl, and t-butyl), pentyl, hexyl, heptyl, octyl, decyl, dodecyl, and branched alkyl groups of 5 to 12 carbon atoms, and cyclic alkyl groups such as cyclopentyl and cyclohexyl. Alternatively, each R 1may be a methyl group. Alternatively, the polyorganohydrogensiloxane can be linear and subscript a = 2. Alternatively, the amount (b + c) can have a value such that 40 < (b + c) < 110. Alternatively, subscripts b and c can have a value such that 21 < b < 57 and 20 < c < 44.
[0021] The silicon-bonded hydrogen (Si-H) content of the polyorganohydrogensiloxane can be determined according to ASTM E168 using quantitative infrared analysis. When relying on silicon hydrogen addition reactions, the ratio of silicon-bonded hydrogen to alkenyl (vinyl) groups is frequently used to determine the amount of starting material. Generally, this is determined by calculating the total weight % of alkenyl groups (e.g., vinyl) [V] in the starting material and the total weight % of silicon-bonded hydrogen [H] in the starting material, and assuming a molecular weight of 1 for hydrogen and a molecular weight of 27 for vinyl, the molar ratio of silicon-bonded hydrogen to vinyl is 27[H] / [V].
[0022] Examples of polyorganohydrogensiloxanes suitable for use herein are: (i) an alpha, omega-trimethylsiloxy-terminated poly(dimethylsiloxane / methylhydrogenosiloxane), (ii) an alpha, omega-trimethylsiloxy-terminated poly(methylhydrogenosiloxane), and (iii) combinations of two or more thereof.
[0023] Linear polyorganohydrogensiloxanes are also commercially available, such as those available from Gelest, Inc. of Morrisville, Pennsylvania, USA, for example, HMS-071, HMS-993; HMS-301, HMS-031, HMS-991, HMS-992, HMS-993, HMS-082, HMS-151, HMS-013, HMS-053, and HAM-301. Methods of making linear and branched polyorganohydrogensiloxanes suitable for use herein, such as the hydrolysis and condensation of organohalosilanes, are well known in the art, as exemplified in the following patents: U.S. Patent 2,823,218 to Speier et al.; U.S. Patent 3,957,713 to Jeram et al.; U.S. Patent 4,329,273 to Hardman et al.; U.S. Patent 4,370,358 to Hayes et al.; U.S. Patent 4,707,531 to Shirahata; and U.S. Patent 5,310,843 to Morita.
[0024] The starting material C) is a hydrosilylation reaction catalyst. This catalyst will facilitate the reaction between the alkenyl groups in A) the alkenyloxy-terminated, aryl-terminated glycol ether (and, when present, D) the alkenyl-functional aromatic compound and / or E) the dienyl-terminated siloxane oligomer) and the silicon-bonded hydrogen atoms in B) the polyorganohydrogensiloxane. The catalyst comprises a platinum group metal. The platinum group metal can be selected from the group consisting of platinum, rhodium, ruthenium, palladium, osmium, and iridium. Alternatively, the platinum group metal can be platinum. The hydrosilylation reaction catalyst can be a platinum group metal or a compound or complex of a platinum group metal. For example, the hydrosilylation reaction catalyst can be a compound such as chlorotris(triphenylphosphine)rhodium(I) (Wilkinson's Catalyst), a rhodium diphosphine chelate such as [1,2-bis(diphenylphosphino)ethane]dichlorodirhodium or [1,2-bis(diethylphosphino)ethane]dichlorodirhodium, chloroplatinic acid (Speier's Catalyst), chloroplatinic acid hexahydrate, platinum dichloride, or a complex of such a compound with an alkenyl-functional organopolysiloxane such as a complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane with platinum (Karstedt's Catalyst) or a Pt(0) complex in tetramethyltetravinylcyclotetrasiloxane (Ashby's Catalyst). Alternatively, the compound or complex can be microencapsulated in a matrix or core-shell structure. Hydrosilylation reaction catalysts are known in the art, for example, as described in PCT Patent Application Publication WO 2021 / 081822 and references cited therein. Hydrosilylation reaction catalysts are commercially available, for example, SYL-OFF ™ 4000 Catalyst and SYL-OFF ™ 2700 are available from Dow Silicones, Midland, Michigan, USA.
[0025] The amount of C) the hydrosilylation reaction catalyst is sufficient to catalyze the hydrosilylation reaction of the alkenyl groups in starting material A) (and, when present, starting material D) the aromatic compound) with the silicon-bonded hydrogen atoms of B) the polyorganohydrogensiloxane. The amount of C) the hydrosilylation reaction catalyst can be sufficient to provide 1 ppm to 1,000 ppm of platinum group metal, based on the combined weight of the starting materials A), B), C) (and, when present, D) and / or E) used in the process. Alternatively, the amount of C) the hydrosilylation reaction catalyst can be sufficient to provide 2 ppm to 50 ppm, alternatively 2 ppm to 10 ppm, of platinum group metal, on the same basis.
[0026] Starting material D) is an alkenyl-functional aromatic compound, which can optionally be added during the process for synthesizing the SPE copolymer. Starting material D) is different from starting material A). Starting material D) can have formula D1): where each R is independently selected from the group consisting of H, a halogen atom, OH, methyl, and methoxy; D' is a covalent bond, a group of formula -CH2-, or a group of formula -CH2-O-; and R" is H or methyl. Alternatively, each R can be H or methyl. Alternatively, each R can be H.
[0027] Alternatively, starting material D) can have formula D2): where D' and R" are as described and exemplified above.
[0028] For example, the D) alkenyl-functional aromatic compound can be selected from the group consisting of styrene, a-methylstyrene, eugenol, allylbenzene, allyl phenyl ether, 2-allylphenol, 2-chlorostyrene, 4-chlorostyrene, 4-methylstyrene, 3-methylstyrene, 4-tert-butylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, and 2,4,6-trimethylstyrene. Alternatively, starting material D) can be a-methylstyrene, which is commercially available from, for example, Sigma Aldrich, Inc. of St. Louis, Missouri, USA. Those skilled in the art will recognize that starting material D) can optionally include a free radical polymerization inhibitor.
[0029] Starting material D) is optional, and thus, it can be absent, i.e., the amount used can be 0. Alternatively, when starting material D) an alkenyl-functional aromatic compound is present, the amount of D) alkenyl-functional aromatic compound can be sufficient to provide a molar ratio of alkenyl groups from starting material D) to silicon-bonded hydrogen atoms of starting material B) of > 0 / 1 to 0.98 / 1.
[0030] Starting material E) is an optional dienyl-terminated siloxane oligomer of the following formula: where R 1 As described above, each R 5 is an alkenyl group of 2 to 6 carbon atoms independently selected, and subscript m is 0 or 1. Alternatively, each R 5 may be independently selected from a vinyl group, an allyl group, or a hexenyl group. Alternatively, subscript m can be 0. Examples of suitable oligomers include divinyltetramethyldisiloxane (M Vi M Vi ), which is available from Dow Chemical Company.
[0031] Starting material E) is optional. The amount of starting material E) can be sufficient to provide a molar ratio of alkenyl groups from starting material E) to silicon-bonded hydrogen atoms of starting material B) of > 0 / 1 to 0.1 / 1, alternatively 0.001 / 1 to 0.002 / 1. Alternatively, starting material E) can be omitted.
[0032] Starting material F) is an optional solvent. A solvent can be added to facilitate the introduction of certain starting materials, such as C) the hydrosilylation reaction catalyst. Solvents that can be used herein are solvents that aid in fluidizing the starting materials but do not substantially react with the starting materials. The solvent can be selected based on the solubility of the starting materials and the volatility of the solvent. Solubility refers to the solvent being sufficient to dissolve and / or disperse the starting materials.
[0033] Suitable solvents include polyorganosiloxanes having a suitable vapor pressure, such as hexamethyldisiloxane, octamethyltrisiloxane, hexamethylcyclotrisiloxane, and other low molecular weight polyorganosiloxanes, such as DOWSIL ™ 200 fluids and DOWSIL ™ OS fluids, available from Dow Inc.
[0034] Alternatively, the solvent can include an organic solvent. The organic solvent can be an alcohol, such as methanol, ethanol, isopropanol, butanol, or n-propanol; a ketone, such as acetone, methyl ethyl ketone, or methyl isobutyl ketone; an aromatic hydrocarbon, such as benzene, toluene, ethylbenzene, or xylene; an aliphatic hydrocarbon, such as heptane, hexane, or octane; a glycol ether, such as propylene glycol methyl ether, dipropylene glycol methyl ether, propylene glycol n-butyl ether, propylene glycol n-propyl ether, or ethylene glycol n-butyl ether; a halogenated hydrocarbon, such as dichloromethane, 1,1,1-trichloroethane, or dichloromethane; chloroform; dimethyl sulfoxide; dimethylformamide, acetonitrile; tetrahydrofuran; petroleum solvent; mineral spirits; naphtha; N-methylpyrrolidone; or a combination thereof.
[0035] The amount of solvent will depend on various factors, including the type of solvent selected and the amount and type of other starting materials selected for the process. However, the amount of solvent can range from 1% to 99%, alternatively 2% to 90%, based on the weight of all starting materials used in step 1).
[0036] The SPE copolymer can be prepared by the above-described process, and the SPE copolymer will be described in further detail below. The SPE copolymer comprises the unit formula: (R 1 3SiO 1 / 2 ) a (R 1 2SiO 2 / 2 ) b (R 1 R 2 SiO2 / 2 ) c wherein subscripts a, b, and c and R 1 are as described above. In the unit formula of the SPE copolymer, each R 2 is independently selected from the group consisting of H, formula E1'), formula D1'), and formula A1'), wherein formula E1') is wherein R 1 and subscript m are as described above, and each R 6 is a divalent hydrocarbon group; formula D1') is wherein R, D', and R" are as described above; and formula A1') is ; wherein X, D, R 3 and subscript n are as described above; and with the proviso that at least one R 2 per molecule is of formula A1'). Those skilled in the art will recognize that formula E1') is a group derived from an E) alkenyl-terminated siloxane oligomer; formula D1') is a group derived from a D) alkenyl-functional aromatic compound; and formula A1') is derived from an A) alkenyloxy-terminated, aryl-terminated glycol ether, each as described above and used in the method of synthesizing the SPE copolymer. Those skilled in the art will further recognize that when the alkenyl group (R 5 ) of starting material E1) undergoes a hydrosilylation reaction with the silicon-bonded hydrogen atoms of starting material B), branching will occur between sites on the molecule of B) polyorganohydrogensiloxane and / or between different molecules of polyorganohydrogensiloxane, such that both ends of the group of formula E1') are bonded to silicon atoms through hydrosilylation of the alkenyl group of starting material (E) with silicon-bonded hydrogen atoms from B) polyorganohydrogensiloxane. Formula E1') can impart branching to the SPE copolymer.
[0037] Alternatively, in the above unit formula, each R 2 may be independently selected from the group consisting of H, formula D1'), and formula A1'). Alternatively, each R 2 may be independently selected from the group consisting of formula D1') and formula A1'). Alternatively, each R 2 may be an independently selected group of formula A1').
[0038] Alternatively, each R can be H, and formula D1') can be formula D2'): wherein R" and D' are as described above.
[0039] Alternatively, each R 3 may be hydrogen, and formula A1') can be formula A2'): wherein X, D, and subscript n are as described above.
[0040] The above method can be used to control the properties of the resulting SPE copolymer, for example by varying the selection of B) polyorganohydrogensiloxane and varying the amount of silicon-bonded hydrogen atoms, and by varying the amount of starting material A) (and, when present, starting materials D) and / or E)). However, the method can be used to produce an SPE copolymer having one or more of the following properties: > 50 mole % R 2 All instances of R 2 All instances of R 2 The balance of all instances of R 2 Each instance of R 2 All instances of R 2 All instances of R 2 The balance of all instances of R 2 All instances of R 2 Each instance of R
[0041] As disclosed in, for example, U.S. Patent 6,858,663, the SPE copolymers can be used as defoamers for aqueous coating systems and printing inks, in addition to or in place of the siloxanediol copolymers described therein. Alternatively, the SPE copolymers described herein can be used as defoamers, neat or in a foam control formulation. For example, the SPE copolymers described herein can be used in addition to or in place of the siloxane polymers or copolymers in any of the foam control formulations of U.S. Patents 6,521,586; 7,105,581; 7,550,514; 7,566,750; 7,619,043; 8,222,303; and 9,518,003. Alternatively, the SPE copolymers can be used as defoamers, neat or in a foam control formulation, in liquid laundry detergent compositions, such as clear liquid laundry detergents. For example, the SPE copolymers can be used in liquid laundry detergents, such as those described in European Patent 3 210 663 and U.S. Patent 10,407,647.
[0042] The foam control formulation can comprise: A) the above-described SPE copolymer; B) a hydrophobic filler; and C) a silicone resin. The foam control formulation can optionally further comprise additional starting materials, in addition to or in place of the hydrophobic filler and the silicone resin.
[0043] Starting material B) that can be used in foam-controlling formulations is a hydrophobic filler. Hydrophobic fillers include inorganic fillers such as silica, quartz powder, zeolite, Al₂O₃, TiO₂, ZrO₂, and combinations thereof, such as aluminosilicates. Alternatively, the hydrophobic filler includes silica. Silica may include pyrolytic silica or precipitated silica. Silica may have a minimum molecular weight of 50 μm. 2 / g, and in other locations 50m² / g to 500m² 2 Specific surface area per g. For example, a specific surface area of 90 m² / g to 300 m² / g can be used. 2 Precipitated silica or pyrolytic silica with a specific surface area of / g. Some of the fillers mentioned above are not hydrophobic in nature, but can be used if made hydrophobic. Treating fillers to make them hydrophobic can be done in situ (i.e., when dispersed in a solvent or together with other starting materials used to prepare the foam control formulation), or by pretreating the filler before mixing it with other starting materials in the foam control formulation. Fillers can be treated, for example, by treatment with fatty acids or by using methyl-substituted organosilicon materials. Suitable hydrophobic agents include polydimethylsiloxanes, dimethylsiloxane polymers terminated with silanol or silicon-bonded alkoxy groups, hexamethyldisilazane, hexamethyldisilazane, and organosilicon resins, such as MQ resin described below. Hydrophobicity can be achieved at a temperature of at least 80°C. Alternatively, MQ resin can be used as a hydrophobic agent for both organosilicon resins and silica fillers. Silica fillers can have an average particle size of 0.5 μm to 50 μm, alternatively 2 μm to 30 μm, and alternatively 5 μm to 25 μm. Silica fillers are known and commercially available in both hydrophilic and hydrophobic forms. Suitable hydrophobic fillers are disclosed, for example, in EP Patent Publication 3,210,663 A, U.S. Patent 6,521,586, and U.S. Patent 11,318,182. The amount of hydrophobic filler (e.g., silica) in the foam control formulation can be from 0.5% to 50% by weight, alternatively 1% to 15% by weight, alternatively 1% to 10% by weight, and alternatively 2% to 8% by weight, based on the weight of A) the SPE copolymer. In addition, the amounts of B) filler and C) silicone resin may be sufficient to provide a weight ratio of 1 / 10 to 20 / 1, alternatively 1 / 5 to 10 / 1, and alternatively 1 / 2 to 6 / 1 of C) silicone resin / B) filler.
[0044] In foam control formulations, C) the silicone resin may comprise, alternatively substantially comprise, or alternatively comprise: Formula R 4 3SiO 1 / 2 The monofunctional (M) unit, where each R 4are independently selected monovalent hydrocarbon groups; and tetrafunctional (Q) units of the formula SiO 4 / 2 4 Examples of suitable monovalent hydrocarbon groups for R 4 may be independently selected from the group consisting of methyl and phenyl. Alternatively, each R 4 may be methyl. When prepared, the silicone resin comprises the M and Q units described above, and the silicone resin further comprises units having silanol (silicon-bonded hydroxyl) groups and can comprise new pentamers of the formula Si(OSiR 4 3)4, where R 4 as described above. As described in U.S. Patent 9,593,209, column 32, reference Example 2, Si 29 Nuclear magnetic resonance (NMR) spectroscopy can be used to measure the molar ratio of M units and Q units, where the ratio is expressed as {M(resin) + (M(new pentamer)} / {Q(resin) + Q(new pentamer)}, and represents the molar ratio of the total number of triorganosiloxy groups (M units) in the resin and new pentamer portion of the silicone to the total number of silicate groups (Q units) in the resin and new pentamer portion. The silicone resin can comprise amounts of M units and Q units such that the molar ratio of M units to Q units (M / Q ratio) is 0.4 / 1 to 2.5 / 1, alternatively 0.4 / 1 to 1.1 / 1, and alternatively 0.5 / 1 to 0.8 / 1. For example, the M / Q ratio can be selected to tailor the silicone resin for different applications, for example, the M / Q ratio can be 0.5 / 1 to 0.8 / 1 when the suds control formulation is used in a laundry detergent composition. In addition to the M units and Q units described above, the silicone resin can optionally further comprise trifunctional (T) units of the formula R 4 SiO 3 / 2 and / or difunctional (D) units of the formula R 4 2SiO 2 / 2 where R 4 as described above. Alternatively, no more than 20% of all units in the silicone resin are D units.
[0045] The Mn of the silicone resin depends on various factors, including the presence of R 4 The type of hydrocarbyl group represented. When the peak representing the new pentamer is excluded from the measurement, the Mn of the silicone resin refers to the number average molecular weight measured using GPC according to the procedure in U.S. Patent 9,593,209, column 31, Reference Example 1. The Mn of the silicone resin can be greater than 3,000 g / mol, alternatively > 3,000 g / mol to 12,000 g / mol. Alternatively, the Mn of the silicone resin can be 4,500 g / mol to 7,500 g / mol. Alternatively, the silicone resin can have a Mw of > 6,000 g / mol, alternatively > 9,000 g / mol, alternatively at least 13,500 g / mol, while at the same time the silicone resin can have a Mw of at most 36,000 g / mol, alternatively at most 24,000 g / mol, alternatively at most 22,500 g / mol, and alternatively at most 15,000 g / mol.
[0046] U.S. Patent 8,580,073, column 3, line 5 to column 4, line 31 is hereby incorporated by reference for disclosing silicone resins suitable for use in the foam control formulations herein. The silicone resins are prepared by any suitable method such as co-hydrolysis of corresponding silanes or by a silica hydrosol capping process. The silicone resins can be prepared by a silica hydrosol capping process such as those disclosed in U.S. Patent 2,676,182 to Daudt et al.; U.S. Patent 4,611,042 to Rivers-Farrell et al.; and U.S. Patent 4,774,310 to Butler et al. The above Daudt et al. process involves reacting a silica hydrosol under acidic conditions with a hydrolyzable triorganosilane such as trimethylchlorosilane, a siloxane such as hexamethyldisiloxane, or mixtures thereof, and recovering a silicone resin having M units and Q units. The resulting silicone resin typically contains 2 to 5 weight percent hydroxyl groups.
[0047] The silicone resins prepared as described above typically contain silicon-bonded hydroxyl groups, i.e., have the formula HOSi 3 / 2 and / or (HO) x R 4 (3-x) SiO 1 / 2where subscript x is 1, 2, or 3. The organosilicon resin can include up to 2% silicon-bonded hydroxyl groups. The concentration of silicon-bonded hydroxyl groups present in the polyorganosilicate resin can be determined according to ASTM Standard E-168-16 using FTIR spectroscopy. For certain applications, it can be desirable for the amount of silicon-bonded hydroxyl groups to be less than 0.7%, alternatively less than 0.3%, alternatively less than 1%, and alternatively from 0.3% to 0.8%. In processes that include reacting the organosilicon resin with a silane, disiloxane, or disilazane containing appropriate end groups, the silicon-bonded hydroxyl groups formed during the preparation of the organosilicon resin can be converted to trihydrocarbylsiloxy groups, such as trimethylsiloxy groups (the process can be referred to as capping, resulting in a capped organosilicon resin). The silane containing hydrolysable groups can be added in a molar excess of the amount required to react with the silicon-bonded hydroxyl groups on the organosilicon resin.
[0048] Alternatively, the organosilicon resin can further include 2% or less, alternatively 0.7% or less, and alternatively 0.3% or less, and alternatively from 0.3% to 0.8% of units represented by the formula XSiO 3 / 2 and / or XR 4 2SiO 1 / 2 where R 4 As described above, and X represents a hydrolysable substituent such as a hydroxyl or alkoxy group. The organosilicon resin can be capped to reduce the content of hydrolysable substituents by reacting the product of Daudt et al. with a capping agent containing unsaturated organic groups and a capping agent containing no aliphatic unsaturation. Examples of capping agents include, but are not limited to, silazanes, siloxanes, and silanes. Suitable organosilicon resins can be as described in, for example, EP Patent Publication 3210663A, U.S. Patent Application Publication 2009 / 0137446, and U.S. Patent 6521586.
[0049] The silicone resin can be present in the foam control formulation from 1 wt% to 50 wt%, alternatively from 2 wt% to 30 wt%, and alternatively from 4 wt% to 15 wt%, based on the weight of A) the SPE copolymer. The silicone resin can be added to the foam control formulation as a solution in a non-volatile solvent (e.g., an alcohol such as dodecanol or 2-butyl-octanol, or an ester such as octyl stearate). A resin solution prepared in a volatile solvent (e.g., xylene) can be combined with a non-volatile solvent, and the volatile solvent can be removed by stripping or by other forms of separation. The non-volatile solvent can optionally remain in the foam control formulation. Alternatively, the silicone resin can be dissolved in an equal amount or less of non-volatile solvent, alternatively no more than 50% by weight of the silicone resin. Alternatively, the silicone resin can be dissolved in a non-volatile solvent in an amount from 50% to 90%, in an amount from 10 wt% to 50 wt% of the combination of silicone resin and solvent. Alternatively, the silicone resin can be added as a solution in a volatile solvent, which is then stripped of the solvent. Alternatively, the silicone resin can be added to the foam control formulation in the form of solid particles, e.g., spray-dried particles. Spray-dried silicone resins are commercially available, e.g., having an average particle size from 10 μm to 200 μm.
[0050] The foam control formulation can optionally further comprise additional starting materials, such as a solvent exemplified by polypropylene glycol, a water-dispersible carrier, a water-miscible liquid, a binder, a sealant, a cyclic siloxane, a thickener, water, a surfactant, a preservative, a water-insoluble organic compound, or a combination of two or more of them. The water-insoluble organic compound has a boiling point > 100°C at ambient pressure, and is exemplified by mineral oil, natural oil, isoparaffin, polyisobutylene, fatty acid esters such as octyl stearate and dodecyl palmitate, and organic waxes (e.g., polyethylene wax and microcrystalline wax), salts of aliphatic carboxylic acids. The amount of additional starting materials depends on various factors, including the desired end use of the foam control formulation, however, the additional starting materials can be used in the foam control formulation from 0 parts by weight to 1000 parts by weight per 100 parts by weight of the combined weight of A) the SPE copolymer, B) the hydrophobic filler, and C) the silicone resin. Suitable optional starting materials that can be added are exemplified by those disclosed in U.S. Patents 6,521,586; 7,550,514; 10,407,647; and 11,383,182.
[0051] The anti-foam formulation can be prepared in any convenient manner, such as by mixing the starting materials under shear. The amount of shear is sufficient to provide good dispersion of B) the hydrophobic filler and C) the silicone resin in A) the SPE copolymer, but insufficient to break up the particles of B) the filler and / or C) the silicone resin, thereby possibly reducing their effectiveness, or exposing non-hydrophobic surfaces. In cases where it is desired to make the filler hydrophobic in situ, the method of manufacture of the anti-foam formulation can include a heating stage, optionally under reduced pressure, in which the filler and treating agent are mixed together in some or all of A) the SPE copolymer, and optionally in the presence of a suitable catalyst, if useful. The anti-foam formulation can be provided as a simple mixture comprising A), B) and C), and any optional additional starting materials as described above. Alternatively, the anti-foam formulation can be provided in alternative forms, such as a solution, solid, dispersion or emulsion.
[0052] For example, the anti-foam formulation can be provided as an emulsion, for example when the anti-foam formulation is to be used in an aqueous composition such as a liquid laundry detergent composition. For example, such an emulsion can comprise a dispersed phase comprising the SPE copolymer (as described above) in an amount of from 5 wt% to 80 wt% based on the weight of the emulsion; a continuous phase comprising water, a surfactant and optionally an additive selected from the group consisting of a preservative, a viscosity modifier, a protective colloid and a thickener. As described above, the dispersed phase can optionally further comprise B) the hydrophobic filler and C) the silicone resin. The emulsion can be prepared by any convenient means, such as those disclosed in U.S. Patent 6,521,586 and references cited therein, by varying the appropriate starting materials.
[0053] Alternatively, the anti-foam formulation can be provided as a water-dispersible composition, in which the A) SPE copolymer, B) hydrophobic filler and C) silicone resin are dispersed in a water-dispersible carrier such as an alkylene glycol or a mineral oil. Alternatively, due to the presence of the group of formula A1') a separate water-dispersible carrier can not be necessary, and the A) SPE copolymer can be used neat as an anti-foam agent. Alternatively, the anti-foam formulation can be provided in solid form, such as a powder or granule. Alternative forms of the anti-foam formulation can be prepared by varying the appropriate starting materials as described in U.S. Patent 6,521,586 and references cited therein.
[0054] The SPE copolymer (neat or in an anti-foam formulation) can be incorporated into a cleaning composition. Such cleaning compositions can be provided in a variety of forms, including but not limited to liquid, gel, paste, bar, granular and powder forms. Such cleaning compositions can be used in a variety of cleaning applications, including but not limited to laundry, cookware and dishware (including dish and flatware), hard surface and personal care (such as body and hair washing).
[0055] Alternatively, the cleaning composition may be a laundry detergent composition, such as a liquid laundry detergent composition. The laundry detergent composition comprises i) the aforementioned SPE copolymer or the aforementioned foam control agent (which contains an SPE copolymer), and ii) a detergency surfactant. Representative detergency surfactants are known in the art and are described, for example, in McCutcheon's Emulsifiers and Detergents, 1989 Annual (published by MC Publishing Co.). Suitable surfactants include: nonionic (e.g., polysaccharides, oxylates, amine oxides, fatty acid amides), amphoteric surfactants, zwitterionic surfactants, cationic (alkylammonium salt) surfactants, and anionic (e.g., sulfonates, polyalkoxylated carboxylates) surfactants. The laundry detergent composition may optionally further comprise additional starting materials selected from the group consisting of: anti-redeposition agents, brighteners, chelating agents, enzymes, antibacterial agents, solvents, pH adjusters, opacifiers, fragrances, dyes, color stabilizers, bactericides, soil release agents, softeners, soaps, carriers, builders, structuring agents, additives, water-soluble growth promoters, dispersants, rheology modifiers, and combinations of two or more of these. The laundry detergent composition may comprise 0.001% to 5.0% by weight, alternatively 0.01% to 4.0% by weight, and alternatively 0.01% to 2.0% by weight of the aforementioned SPE copolymers or foam control agents; the balance of the laundry detergent is a detergency surfactant and optionally one or more of the aforementioned additional starting materials. The aforementioned SPE copolymers and / or foam control agents can be used in known detergent compositions, such as those disclosed in U.S. Patents 6,521,586 and 11,383,182.
[0056] Examples
[0057] The following embodiments are provided to illustrate the invention to those skilled in the art, and these embodiments should not be construed as limiting the scope of the invention as set forth in the claims. The starting materials used in these embodiments are defined in Table 1 below.
[0058]
[0059] In this Example 1, (2-(allyloxy)ethoxy)benzene (A-1)EPh allyl ether was prepared as follows: A 3-L round-bottom flask equipped with a top stirrer, a water-cooled condenser, a feeding funnel, and a nitrogen bubbler was placed in a temperature-controlled heating mantle and loaded with 804.6 g (5.82 mol) of DOWANOL. ™EPh, 19.39 g of Aliquat ™ 336 and 621.65 g (8.12 moles) of allyl chloride. The clear yellow solution was equipped with a Teflon ™ paddle stirrer, and 833.1 g (10.4 moles) of 50% aqueous sodium hydroxide was charged dropwise over about 1 hour. The temperature rose from 21 °C to 50 °C during the addition. A smooth white slurry formed. The mixture was warmed to 65-70 °C. GC analysis of the upper organic phase after three hours found 6.0 area% allyl chloride, 0.43 area% DOWANOL ™ EPh, and 90.3 area% EPh allyl ether. After cooling to ambient temperature, the white slurry was diluted with 665.5 g of water, the mixture was transferred to a 3-L separatory funnel, and the lower aqueous phase (1666.4 g) containing some heavy white solid precipitate was removed. The organic phase was washed with 205.3 g of water, and the lower aqueous phase (245.6 g) was removed. The organic phase (1173.1 g) was mixed with 14.0 g of MagSil, and the slurry was filtered under vacuum through filter paper to give 1137.7 g of a clear yellow filtrate. The filtrate was charged to a 2-L round bottom flask equipped with a magnetic stirrer and a 6" high vacuum jacketed and silvered Vigreux column with a water-cooled distillate condenser. A temperature-controlled heating mantle was attached to the flask, and vacuum was applied using a dry ice-protected Edwards vacuum pump. The forecut (10.41 g) was collected at 100 °C top temperature and 112 °C pot temperature at 1.9 torr. The product fraction was collected in a 2-L receiving flask at 98-105 °C top temperature, 110-117 °C pot temperature, and 1.5-2 torr pressure until no more distillate could be collected to give 984.4 g (5.52 moles, 94.9% yield) of (2-allyloxy)ethoxybenzene (2-allyloxyethyl phenyl ether, CAS Number 93066-80-9) >99 area% pure by GC analysis.
[0060] In this Example 2, (2-(allyloxy)propoxy)benzene (A-2) PPh allyl ether) was prepared as follows: A 3-L round bottom flask with an overhead stirrer, water-cooled condenser, addition funnel, and nitrogen bubbler was placed in a temperature-controlled heating mantle and charged with 872.2 g (5.73 moles) of DOWANOL ™ PPh, 22.43 g of Aliquat ™ 336 and 604.4 g (7.90 moles) of allyl chloride. GC analysis found 33.2 area% allyl chloride and 62.0 area% DOWANOL ™ PPh. The clear yellow solution was equipped with a Teflon ™With impeller stirring, 820.7 g (10.3 mol) of a 50% sodium hydroxide aqueous solution was added dropwise over approximately 1 hour. During the addition, the temperature rose from 21°C to 37°C, and a white slurry formed. The mixture was stirred and gently warmed to 50°C to 60°C; the maximum temperature reached was 70°C. Two hours after the alkali addition was complete, GC analysis of the upper organic phase revealed 23.4 area % allyl chloride and 37.9 area % DOWANOL. ™ PPh and 36.4 area % PPh allyl ether. An additional 6.4 g of Aliquat was added. ™ 336. GC analysis of the upper organic phase after stirring overnight at 55°C revealed 4.1 area % allyl chloride and 3.8 area % DOWANOL. ™ PPh and 85.0 area % PPh allyl ether. An additional 2.47 g of Aliquat was added. ™ 336. GC analysis after three hours at 55°C showed no additional conversion. Heating to 70°C to 75°C did not improve the conversion. After cooling to ambient temperature, the white slurry was diluted with 826.3 g of water, the mixture was transferred to a 3-L separatory funnel, and the lower aqueous phase (1830.9 g) containing some heavy white solid precipitate was removed. The organic phase (1220.3 g) was mixed with 34.1 g of MagSil, and the slurry was filtered through filter paper under vacuum to obtain 1140.1 g of clear yellow filtrate. The filtrate was transferred to a 2-L round-bottom flask equipped with a magnetic stirrer, a 6" high-vacuum jacket, and a silver-plated Vigreux column (with a water-cooled distillate condenser). A temperature-controlled heating mantle was attached to the flask, and a vacuum was applied using a dry-ice-protected Edwards vacuum pump. The fore fraction (92.55 g, 93.8 area % PPh allyl ether as determined by GC) was collected at a top temperature of 40°C to 100°C and a tank temperature of 100°C to 115°C at 2.5 Torr. The product fraction was collected in a 2-L receiving flask at a top temperature of 96°C to 98°C, a tank temperature of 105°C to 110°C, and a pressure of 2 Torr to 2.5 Torr until no more distillate could be collected, yielding 904.0 g (4.70 mol, 82.0% yield) of PPh with a purity of 96.6 area % (3.3 area % DOWANOL) as determined by GC. ™ (PPh) of (2-(allyloxy)propoxy)benzene.
[0061] In this Example 3, 2-(2-allyloxy)ethoxy)ethoxy)benzene was prepared as follows: A 2-L round-bottom flask equipped with a top-mounted stirrer, a water-cooled condenser, a feeding funnel, and a nitrogen bubbler was placed in a temperature-controlled heating mantle, and 403.92 g of phenylene glycol ether (approximately 70% DOWANOL) was added. ™DiEPh, 15% DOWANOL ™ EPh, 8.15 g of Aliquat ™ 336 and 265.54 g of allyl chloride. GC analysis found 34.2 area% allyl chloride, 12.9 area% DOWANOL ™ EPh and 52.9 area% DOWANOL ™ DiEPh. The clear yellow solution was diluted with Teflon ™ paddle stirrer, warmed to 50 °C, and charged dropwise with 408 g of 50% aqueous sodium hydroxide solution. During the addition, the temperature rose to 60 °C. A smooth white slurry formed. The mixture was warmed to 60 °C to 70 °C. GC analysis of the upper organic phase after three hours found 5.9 area% allyl chloride, 17.4 area% EPh allyl ether, 19.4 area% unreacted DOWANOL ™ DiEPh and 62.9 area% DiEPh allyl ether. GC analysis of the upper organic phase after stirring overnight found 0.67 area% allyl chloride, 18.0 area% EPh allyl ether, 0.94 area% unreacted DOWANOL ™ DiEPh and 65.4 area% DiEPh allyl ether. After cooling to ambient temperature, the white slurry was diluted with 400 mL of water, the mixture was transferred to a 3-L separatory funnel, and the lower aqueous phase (874.4 g) containing some heavy white solid precipitate was removed. The organic phase was washed with 100 mL of water, and 112.0 g of the aqueous phase was removed. The organic phase (541.36 g) was combined with 25.8 g of anhydrous magnesium sulfate, and the slurry was filtered under vacuum through filter paper to give 492.93 g of a clear yellow filtrate. The filtrate was charged to a 1-L round bottom flask equipped with a magnetic stirrer and a short path distillation head with a water-cooled distillate condenser. A temperature-controlled heating mantle was attached to the flask, and vacuum was applied using a dry ice-protected Edwards vacuum pump. The product fraction was collected in a 1-L receiving flask at a top temperature of 115 °C to 127 °C, a pot temperature of 133 °C to 135 °C, and a pressure of 1.3 torr to 4.4 torr until no more distillate could be collected, to give 429.91 g (88% yield, assuming 100% pure DiEPh) of (2-(2-allyloxy)ethoxy)ethoxy)benzene (20.3 area% EPh allyl ether; 71.2 area% DiEPh allyl ether by GC analysis).
[0062] In this Example 4, (2-(2-allyloxy)propoxy)propoxy)benzene was prepared as follows: A 2-L round-bottom flask equipped with a top-mounted stirrer, a water-cooled condenser, a feeding funnel, and a nitrogen bubbler was placed in a temperature-controlled heating mantle and filled with 429.91 g of phenylene glycol ether (95% DiPPh, 5% DOWANOL). ™ PPh), 8.92g Aliquat ™ 336 and 243.0 g of allyl chloride. GC analysis revealed 28.8 area % allyl chloride and 3.4 area % DOWANOL. ™ PPh and 62.3 area % DiPPh. The clear yellow solution was treated with Teflon. ™ With impeller stirring, 372.0 g of a 50% sodium hydroxide aqueous solution was added dropwise over 17 minutes. The temperature was increased from 25°C to 34°C. A smooth white slurry was formed. The mixture was heated to 60°C to 70°C. GC analysis of the upper organic phase after three hours revealed 5.7 area % allyl chloride, 4.7 area % PPh allyl ether, 10.3 area % DiPPh, and 68.2 area % DiPPh allyl ether. GC analysis of the upper organic phase after stirring overnight revealed 1.9 area % allyl chloride, 4.7 area % PPh allyl ether, 7.6 area % DiPPh, and 73.6 area % DiPPh allyl ether. After cooling to ambient temperature, the white slurry was diluted with 532.58 g of water, the mixture was transferred to a 3-L separatory funnel, and the clear lower aqueous phase (984.6 g) was removed. The organic phase was washed with 159.31 g of water, and 151.9 g of aqueous phase was removed. The organic phase (666.88 g) was mixed with 39.52 g of anhydrous magnesium sulfate, and the slurry was filtered through filter paper under vacuum to obtain 522.54 g of clear yellow filtrate. The filtrate was transferred to a 1-L round-bottom flask equipped with a magnetic stirrer and a short-path distillation head (with a water-cooled distillate condenser). A temperature-controlled heating mantle was attached, and a vacuum was applied using an Edwards vacuum pump protected with dry ice. The product fraction was collected in a 1-L receiving flask at a top temperature of 110°C to 122°C, a tank temperature of 130°C to 135°C, and a pressure of 1 Torr, until no more distillate could be collected, to give 479.83 g (94% yield, assuming 100% purity DiPPh) of (2-(2-allyloxy)propoxy)propoxy)benzene (7.2 area% PPh allyl ether; 79.5 area% DiPPh allyl ether as determined by GC analysis).
[0063] In this Example 5, (2-((2-methylallyl)oxy)ethoxy)benzene (A-5) EPh was prepared as follows: A 3-L round bottom flask with overhead stirrer, water-cooled condenser, addition funnel, and nitrogen sparge was placed in a temperature controlled heating mantle and charged with 800.8 g (5.79 moles) of DOWANOL ™ EPh, 13.42 g of Aliquat ™ 336 and 737.5 g (8.14 moles) of 3-chloro-2-methyl-l-propene. GC analysis found 43.7 area% of 3-chloro-2-methyl-l-propene and 56.0 area% of DOWANOL ™ EPh. The clear yellow solution was diluted with 549.5 g of water, the mixture was transferred to a 3-L separatory funnel, and the lower aqueous phase (1581.5 g) containing some heavy white solid precipitate was removed at 40 °C. The organic phase (1298.7 g) was mixed with 27.65 g of MagSil and the slurry was filtered under vacuum through filter paper to give 1234.2 g of a clear yellow filtrate. The filtrate was charged to a 2-L round bottom flask equipped with a magnetic stirrer and a 6" high vacuum jacketed and silvered Vigreux column with a water-cooled distillate condenser. A temperature controlled heating mantle was attached and vacuum was applied using an Edwards vacuum pump protected with dry ice. The forecut (29.45 g) was collected at a top temperature of 99 °C to 117 °C and a pot temperature of up to 127 °C. The product fraction was collected in a 2-L receiving flask at a top temperature of 116 °C to 117 °C, a pot temperature of 120 °C to 127 °C, and a pressure of 3.9 torr to 4.1 torr until no more distillate could be collected to give 1010.6 g (5.26 moles, 90.7% yield) of (2-((2-methylallyl)oxy)ethoxy)benzene of 99.6 area% purity by GC analysis. ™ paddle stirrer, and 863.0 g (10.8 moles) of 50% sodium hydroxide aqueous solution was charged dropwise over about 1 hour. The temperature rose from 18 °C to 36 °C during the addition. A white slurry formed. The mixture was warmed to 60 °C and allowed to stir overnight. GC analysis of the upper organic phase found 10.3 area% of 3-chloro-2-methyl-l-propene, 0.64 area% of DOWANOL ™ EPh, and 87.6 area% of EPh methylallyl ether. The white slurry was diluted with 549.5 g of water, the mixture was transferred to a 3-L separatory funnel, and the lower aqueous phase (1581.5 g) containing some heavy white solid precipitate was removed at 40 °C. The organic phase (1298.7 g) was mixed with 27.65 g of MagSil and the slurry was filtered under vacuum through filter paper to give 1234.2 g of a clear yellow filtrate. The filtrate was charged to a 2-L round bottom flask equipped with a magnetic stirrer and a 6" high vacuum jacketed and silvered Vigreux column with a water-cooled distillate condenser. A temperature controlled heating mantle was attached and vacuum was applied using an Edwards vacuum pump protected with dry ice. The forecut (29.45 g) was collected at a top temperature of 99 °C to 117 °C and a pot temperature of up to 127 °C. The product fraction was collected in a 2-L receiving flask at a top temperature of 116 °C to 117 °C, a pot temperature of 120 °C to 127 °C, and a pressure of 3.9 torr to 4.1 torr until no more distillate could be collected to give 1010.6 g (5.26 moles, 90.7% yield) of (2-((2-methylallyl)oxy)ethoxy)benzene of 99.6 area% purity by GC analysis.
[0064] In this Example 6, (2-((2-methylallyl)oxy)propoxy)benzene(A-6)PPh methylallyl ether was prepared as follows: A 3-L round-bottom flask equipped with a top stirrer, a water-cooled condenser, a feeding funnel, and a nitrogen bubbler was placed in a temperature-controlled heating mantle and loaded with 828.5 g (5.44 mol) of DOWANOL. ™ PPh and 672.2 g (7.42 mol) of 3-chloro-2-methyl-1-propene. GC analysis revealed 40.0 area % of 3-chloro-2-methyl-1-propene and 60.0 area % of DOWANOL. ™ PPh. The clarified solution was treated with Teflon. ™ Stir with the paddle and add 20.00g of Aliquat. ™ 336, and heated to 44°C, 808.2 g (10.1 mol) of a 50% sodium hydroxide aqueous solution was added dropwise over approximately 1.5 hours. During the addition, the temperature was raised to 49°C, and the heating mantle was removed to control the temperature. A white slurry was formed. The mixture was stirred at 50°C to 60°C. Two hours after the alkali addition was complete, GC analysis of the upper organic phase revealed 25.4 area % 3-chloro-2-methyl-1-propene and 31.7 area % DOWANOL. ™ PPh and 40.9 area % PPh methyl allyl ether. GC analysis of the upper organic phase after stirring overnight at 50°C revealed 9.0 area % 3-chloro-2-methyl-1-propene and 8.7 area % DOWANOL. ™ PPh and 78.7 area % PPh methyl allyl ether. An additional 12.44 g of Aliquat was added. ™ GC analysis of the upper organic phase after stirring overnight at 50°C with 336 g and 99.9 g of a 50% sodium hydroxide aqueous solution revealed 4.2 area % 3-chloro-2-methyl-1-propene and 2.7 area % DOWANOL. ™PPh and 87.6 area % of PPh methylallyl ether. After cooling to ambient temperature, the white slurry was diluted with 863.6 g of water, the mixture was transferred to a 3-L separatory funnel, and the lower aqueous phase containing some heavy white solid precipitate (1946.2 g) was removed. The organic phase (1261.6 g) was mixed with 44.4 g of MagSil, and the slurry was filtered under vacuum through filter paper to give 1180.6 g of clear yellow filtrate. The filtrate was charged to a 2-L round bottom flask equipped with a magnetic stirrer and a 6" high vacuum jacketed and silvered Vigreux column with a water-cooled distillate condenser. A temperature-controlled heating mantle was attached to the flask, and vacuum was applied using a dry ice-protected Edwards vacuum pump. The forecut (27.87 g, 21.6 area % PPh methylallyl ether by GC analysis) was collected at 91 °C to 100 °C top temperature and 97 °C to 111 °C pot temperature at 7 torr to 1.9 torr. The product fraction was collected in a 2-L receiving flask at 102 °C to 105 °C top temperature, 119 °C to 142 °C pot temperature, and 1.7 torr to 2.1 torr pressure until no more distillate could be collected to give 1044.6 g (5.06 moles, 93.1 % yield) of (2-((2-methylallyl)oxy)propoxy)benzene of 97.3 area % purity by GC analysis (2.7 area % DOWANOL ™ PPh) at 97.3 °C to 97.9 °C top temperature, 97.3 °C to 97.9 °C pot temperature, and 1.7 torr to 2.1 torr pressure.
[0065] In this Example 7, copolymer sample 1 was synthesized as follows: polyorganohydrogensiloxane (B-1) M2D 38 D H 33, 1 equivalent, 55 g) and the required amount of D-1) AMS (5% of total D-1) AMS (2.16 g, total 43.3 g) were charged into a 250 mL three necked round bottom flask equipped with a condenser, magnetic bar and N2inlet. The contents were stirred at room temperature until a homogenized mixture was obtained. To insert the C-1) catalyst, a solution of 2-0719 was prepared in IPA (5000 ppm). The temperature was set at 100 °C while the catalyst solution was added (amount sufficient to provide 10 ppm Pt) when the temperature reached 70 °C. At T = 100 °C, 10.28 g of D-1) AMS was added. 15 min later a second portion of D-1) AMS (10.28 g) was added with a syringe, after which the catalyst solution was added in an amount sufficient to provide 2 ppm Pt. 15 min later a third portion of D-1) AMS (10.28 g) was added with a syringe, again after which the catalyst solution was added in an amount sufficient to provide 2 ppm Pt. 15 min later a last portion of D-1) AMS (10.28 g) was added with a syringe, after which the catalyst solution was added in an amount sufficient to provide 8 ppm Pt. 5h 30 min later, the temperature was increased to 110 °C and finally the catalyst solution was added in an amount sufficient to provide 4 ppm Pt. 1h 30 min later, the reaction was stopped. The total amount of C-1) catalyst used was sufficient to provide 26 ppm Pt and the total time elapsed was 7h 45 min.
[0066] In this example 8, copolymer sample 2 was synthesized as follows: polyorganohydrogensiloxane (B-1) M2D 38 D H 33 , 1 equivalent, 55 g) and the required amount of A-5) EPh methallyl ether (prepared as described in example 5 above) (2 equivalents, 4.27 g) were charged into a 250 mL three necked round bottom flask equipped with a condenser, magnetic bar and N2inlet. The AMS was added in 4 portions (10.16 g each). The contents were stirred at room temperature until a homogenized mixture was obtained. To insert the catalyst, a solution of C-1) catalyst was prepared in IPA (5000 ppm). The temperature was set at 85 °C while the catalyst solution was added (amount sufficient to provide 12 ppm Pt) when the temperature reached 75 °C. At T = 85 °C, 10.16 g of D-1) AMS was added from a dropping funnel and the temperature was increased to 92.3 °C. Within 5 minutes, the temperature was again decreased to 85 °C, whereby a second portion of D-1) AMS (10.16 g) was added dropwise. As no temperature increase was observed, an additional catalyst solution was inserted (amount sufficient to provide 8 ppm Pt) and the temperature was increased by 27 °C and decreased back to the initial value. This cycle was performed 4 times in total, with an additional catalyst solution inserted at each step (amount providing a total of 24 ppm Pt). 4h 35 min later,1 H-NMR analysis showed that D-1) AMS was depleted in the medium, while SiH sites available for reaction were present. This could be due to accidental leakage of D-1) AMS from the system. Additional D-1) AMS was charged to the reactor (7 equivalents, 9.2 g) after which a catalyst solution was charged in an amount sufficient to provide 12 ppm Pt. The temperature was raised to 105 °C. The reaction was run for an additional 3 hours after which it was complete.
[0067] In this example 9, copolymer sample 9 was synthesized as follows: SiH source (B-1) M2D 38 D H 33 A-6) PPh-methallyl ether (prepared as described in example 6 above, in an amount of 2 equivalents, 4.58 g) were charged to a 250 mL three necked round bottom flask, equipped with a condenser, magnetic bar and N2inlet. D-1) AMS was added in 4 portions (10.16 g each). The contents of the flask were stirred at room temperature until a homogenized mixture was obtained. To insert the catalyst, a solution of C-1) catalyst was prepared in IPA (5000 ppm). The temperature was set at 85 °C while the catalyst solution was added (in an amount sufficient to provide 12 ppm Pt) when the temperature reached 75 °C. The rest of the reaction was carried out in the same way as example 8 to produce copolymer sample 8 (HT210). The addition of the 4 portions of D-1) AMS was completed in 5h 15min, with 26 ppm Pt. The conversion was not complete. The reaction was restarted and heated to 105 °C after which an excess of D-1) AMS (26.2 g) and enough catalyst solution to provide 8 ppm Pt were added. After 6 hours of reaction, the synthesis was complete and the excess D-1) AMS was removed by stripping.
[0068] In this example 10, copolymer sample 10 was synthesized as follows: SiH source (B-1) M2D 38 D H 33, 1 eq, 50 g) and A-6) PPhp-methallyl ether (10% total, 6.9 g) were charged into a 250 mL three necked round bottom flask equipped with a condenser, magnetic bar and N2inlet. The contents were stirred at room temperature until a homogenized mixture was obtained. To insert the catalyst, a solution of C-1) catalyst was prepared in IPA (5000 ppm). The temperature was set at 100 °C while the catalyst solution was added (an amount sufficient to provide 24 ppm Pt) when the temperature reached 75 °C. At T = 100 °C, 15.5 g of A-6) PPhp-methallyl ether was added dropwise. After 1 hour a second portion was added, followed by a third portion after an additional hour. Enough catalyst solution was added to provide 6 ppm Pt as no exotherm was observed. The temperature was raised to 110 °C. 4 mL of toluene was added to help reflux. After a total of 4 h 30 min, a last portion of A-6) PPhp-methallyl ether was added and the reaction was run for an additional 25 minutes before being stopped.
[0069] In this example 11, copolymer sample 11 was synthesized as follows: SiH source (B-1) M2D 38 D H 33, 1 equivalent, 43.4 g) and 10% A-5) EPh P-alkenyl ether (prepared as described in Example 5 above) (5.55 g) was charged into a 250 mL three necked round bottom flask equipped with a condenser, magnetic bar and N2inlet. The contents were stirred at room temperature until a homogenized mixture was obtained. To insert the catalyst, a solution of C-1) catalyst was prepared in IPA (5000 ppm). The temperature was set at 85 °C while the catalyst solution was added (in an amount sufficient to provide 24 ppm Pt) when the temperature reached 75 °C. After reaching T = 85 °C, the first portion of A-5) EPh P-alkenyl ether (12.5 g) was added through a dropping funnel. Over a reaction time of 5 hours, three portions of A-5) EPh P-alkenyl ether were added together with the catalyst solution sufficient to provide 4 ppm additional Pt. The temperature was raised to 100 °C and the reaction was run for an additional 1.5 h before being stopped. The reactor was re-heated to 100 °C. 4 mL of IPA was added together with the last portion of A-5) EPh P-alkenyl ether and an additional amount of catalyst solution sufficient to provide 2 ppm Pt. After 7 hours of reaction time, the reaction was stopped. The reaction was still incomplete. The following day, the reactor was re-heated to 100 °C, 0.6 g of A-5) EPh P-alkenyl ether was added together with an amount of catalyst solution sufficient to provide 4 ppm Pt and the reaction was run for an additional 7 hours. To force completion, the reaction was re-started at 110 °C. An amount of catalyst solution sufficient to provide 2 ppm Pt was added and 9 mL of toluene was added for reflux. The reaction time of 7 hours was completed. Finally, the solvent was stripped and the reaction was complete.
[0070] In this Example 12, copolymer sample 12 was synthesized as follows: SiH source (B-1) M2D 38 D H 33, 1 equivalent, 55 g) and A-2) PPh allyl ether (2 equivalents, 4.69 g) were charged into a 250 mL three necked round bottom flask equipped with a condenser, magnetic bar and N2inlet. The contents were stirred at room temperature until a homogenized mixture was obtained. To insert the catalyst, a solution of C-1) catalyst was prepared in IPA (5000 ppm). The temperature was set at 85 °C while the catalyst solution was added (an amount sufficient to provide 4 ppm Pt) when the temperature reached 75 °C. D-1) AMS (31 equivalents) was added in 4 portions (10.16 g each). The first 2 portions of D-1) AMS were added at 85 °C, an amount of catalyst solution sufficient to provide additional 2 ppm Pt was added each time. The third addition did not require additional catalyst, while an amount of catalyst solution sufficient to provide 2 ppm Pt was added after the last portion. The total reaction time was 5 h 40 m at 10 ppm Pt. However, as observed in the previous case, D-1) AMS was not sufficient. The reactor was heated to 85 °C. D-1) AMS (30 g) was added dropwise to the reactor, followed by an amount of catalyst solution sufficient to provide 8 ppm Pt. After 7 h 30 m, the reaction was stopped and the excess D-1) AMS was stripped.
[0071] In this example 13, copolymer sample 13 was synthesized as follows: SiH source (B-1) M2D 38 D H 33 , 1 equivalent, 55 g) and A-2) PPh allyl ether (2 equivalents, 4.69 g) were charged into a 250 mL three necked round bottom flask equipped with a condenser, magnetic bar and N2inlet. The contents were stirred at room temperature until a homogenized mixture was obtained. To insert the catalyst, a solution of C-1) catalyst was prepared in IPA (5000 ppm). The temperature was set at 85 °C while the catalyst solution was added (an amount sufficient to provide 4 ppm Pt) when the temperature reached 75 °C. D-1) AMS (31 equivalents) was added in 4 portions (10.16 g each). The first 2 portions of D-1) AMS were added at 85 °C, an amount of catalyst solution sufficient to provide additional 2 ppm Pt was added each time. The third addition did not require additional catalyst, while an amount of catalyst solution sufficient to provide 2 ppm Pt was added after the last portion. The total reaction time was 5 h 40 m at 10 ppm Pt. However, as observed in the previous case, D-1) AMS was not sufficient. The reactor was heated to 85 °C. D-1) AMS (30 g) was added dropwise to the reactor, followed by an amount of catalyst solution sufficient to provide 8 ppm Pt. After 7 h 30 m, the reaction was stopped and the excess D-1) AMS was stripped.
[0072] In this example 14, copolymer sample 14 was synthesized as follows: SiH source (B-1) M2D 38 D H 33, 1 equivalent, 50 g) and A-2) PPh allyl ether (7 g, 10% total) were charged into a 250 mL three necked round bottom flask equipped with a condenser, magnetic bar and N2inlet. The contents were stirred at room temperature until a homogenized mixture was obtained. To insert the catalyst, a solution of C-1) catalyst was prepared in IPA (5000 ppm). The temperature was set at 85 °C while the catalyst solution was added (an amount sufficient to provide 4 ppm Pt) when the temperature reached 75 °C. At T = 85 °C, the first portion of A-2) PPh allyl ether (15.8 g) was added dropwise. The same procedure was repeated 4 times. The reaction was completed after approximately 7 hours.
[0073] In this example 15, SPE copolymer sample 15 (SPE-Ph-EO1) was prepared as follows: The hydrosilylation reaction was performed in a 250 mL four necked round bottom flask equipped with a digital overhead stirrer, thermocouple, stopper, condenser and nitrogen inlet. The heating system was through a heating mantle with a J-KEM temperature controller. To the pot was added A-1) EPh allyl ether (7 g, 1st portion, 10%) and M2D 38 D H 33 (45 g). The mixture was heated to 70 °C under nitrogen. Catalyst C-1) catalyst was added (an amount sufficient to provide 4 ppm Pt). This reaction was exothermic and the temperature rose to 98 °C. The temperature was then decreased to 73 °C over 1 h. The 2nd portion of A-1) EPh allyl ether (15 g) was added dropwise through a funnel. The temperature rose to 89 °C and was decreased to 73 °C over 45 min. Another 15 g of A-1) EPh allyl ether was added and the temperature increased to 83 °C over a few minutes. Catalyst C-1) was added in an amount sufficient to provide 4 ppm Pt, the temperature rose to 90 °C and 3 mL of isopropyl alcohol was added to trigger the reaction. After 1 h, the last portion of 15 g of EPh allyl ether was added with an additional amount of C-1) catalyst to provide 4 ppm Pt and the reaction was run for another hour before being stopped.
[0074] In this example 16, sample SPE copolymer sample 16 (SPE-AMS-mPh-PO1) was prepared as follows: First, separate mixtures (monomer blends) were prepared using equal amounts of D-1) AMS and A-6) PPh methallyl ether. The hydrosilylation reaction was performed in a 250 mL four necked round bottom flask equipped with a digital overhead stirrer, thermocouple, stopper, condenser and nitrogen inlet. The heating system was through a heating mantle with a J-KEM temperature controller. To the pot was added the monomer blend (6 g, 1st portion, 10%) and M2D 38 D H 33(55 g). The mixture was stirred under nitrogen for 5 minutes, then the temperature was set to 100 °C. When the temperature reached 70 °C, catalyst C-1) was added in an amount sufficient to provide 12 ppm Pt. The remainder of the mixture of D-1) and A-6) (monomer blend) was added dropwise in 4 different portions (14.85 g each), and the exothermic trend was monitored with an IR probe. Each addition was followed by catalyst C-1) in an amount sufficient to provide 3-6 ppm Pt, which caused a temperature increase. The temperature was allowed to decrease and stabilize to 100 °C before the next monomer blend was added. Overall, the reaction was run for 5 hours, then stopped. The next day, the flask was reheated to 100 °C, and the reaction was run for an additional 3 hours, with C-1) catalyst added in an amount sufficient to provide 3 ppm Pt to complete the reaction (total of 45 ppm Pt). Excess monomer remained in the mixture.
[0075] In this example 17, SPE copolymer sample 17 was prepared as follows: a hydrosilylation reaction was conducted in a 250 mL four-necked round bottom flask, equipped with a mechanical overhead stirrer, a thermocouple, a stopper, a condenser, and a nitrogen inlet. The heating system was through a heating mantle with a PT-100 temperature controller. A-6) PPh methallyl ether (1.25 g, 1st portion, 5%) and 30.01 g of M2D 52.5 D H 21.1The mixture was heated to 75°C under nitrogen. After 25 minutes, when the temperature reached 76°C, a Pt catalyst in IPA (5000 ppm active level) at ± 6 ppm was added. This reaction was exothermic and the temperature rose to 80°C at 27 minutes. The temperature was set to 100°C. At 53 minutes, when the temperature reached 99.3°C, the 2nd portion of A-6) PPh methallyl ether (5.54 g) was added dropwise through the funnel over 5 minutes. At 1 h 02, when the temperature was 101.7°C, a second dose of Pt catalyst in IPA (5000 ppm active level) (0.070 g / ± 5 ppm) was added. At 1 h 04, the temperature reached 108°C. At 2 h 42, when the temperature reached 102.4°C, the 3rd portion of A-6) PPh methallyl ether (6.17 g) was added dropwise through the funnel over 4 minutes. At 2 h 55, when the temperature was 103°C, a third dose of Pt catalyst in IPA (5000 ppm active level) (0.064 g / ± 5 ppm) was added. At 2 h 56, the temperature reached 104.3°C. At 3 h 52, when the temperature reached 100.4°C, the 4th portion of A-6) PPh methallyl ether (5.87 g) was added dropwise through the funnel over 1 minute. At 4 h 05, when the temperature was 102.2°C, a fourth dose of Pt catalyst in IPA (5000 ppm active level) (0.05 g / ± 4 ppm) was added. At 4 h 06, the temperature reached 103.6°C. At 4 h 37, when the temperature reached 103.1°C, the last portion of A-6) PPh methallyl ether (5.89 g) was added dropwise through the funnel over 1 minute. At 6 h 38 and temperature 99.6°C, the reaction was stopped and an H+NMR was performed to see if there were still SiH unreacted. Two days after the reaction restarted and at 1 h 14, when the temperature reached 99.2°C, a Pt catalyst in IPA (5000 ppm active level) at ± 3 ppm was added. At 3 h 57, when the temperature was 98.1°C, the reaction was stopped and another H+NMR was performed. This second NMR analysis confirmed that there were no more SiH reacted. A total of 27.55 ppm of catalyst was used.
[0076] In this example 18, SPE copolymer sample 18 was prepared as follows: the hydrosilylation reaction was performed in a 250 mL four-necked round bottom flask, equipped with a mechanical overhead stirrer, a thermocouple, a stopper, a condenser and a nitrogen inlet. The heating system was through a heating mantle with a PT-100 temperature controller. A-6) PPh methallyl ether (1.25 g, 1st portion, 4%) and 25 g of M2D 23.1 D H 20The mixture was heated under nitrogen. After 16 minutes, when the temperature reached 100.8 °C, a Pt catalyst in IPA (5000 ppm active level) was added ± 6 ppm. This reaction was exothermic and the temperature rose to 107.7 °C at 17 minutes. At 43 minutes, when the temperature reached 97.3 °C, the 2nd portion of A-6) PPh methallyl ether (5.6 g) was added dropwise through the funnel over 8 minutes - the temperature reached 110.2 °C. At 53 minutes, when the temperature was 110.1 °C, a second dose of Pt catalyst in IPA (5000 ppm active level) (0.059 g / ± 6 ppm) was added. At 54 minutes, the temperature reached 112.7 °C. At 2h27, when the temperature reached 105.4 °C, the 3rd portion of A-6) PPh methallyl ether (6.22 g) was added dropwise through the funnel over 4 minutes. At 2h47, when the temperature reached 102 °C, the 4th portion of A-6) PPh methallyl ether (6.54 g) was added dropwise through the funnel over 6 minutes. At 3h33, when the temperature reached 102.4 °C, the 5th portion of A-6) PPh methallyl ether (7 g) was added dropwise through the funnel over 1 minute. At 4h18, when the temperature reached 102.4 °C, the last portion of A-6) PPh methallyl ether (6.84 g) was added dropwise through the funnel over 5 minutes. At 4h56, when the temperature was 102.2 °C, a third dose of Pt catalyst in IPA (5000 ppm active level) (0.03 g / ± 3 ppm) was added. At 5h37 and the temperature was 100.7 °C, the reaction was stopped and an H+NMR was taken to see if there was still SiH unreacted. The next day (26.08.2022), the reaction was restarted and at 3h29, when the temperature reached 103.2 °C, a Pt catalyst in IPA (5000 ppm active level) was added ± 3 ppm. At 5h45, when the temperature was 105 °C, a dose of Pt catalyst in IPA (5000 ppm active level) (0.026 g / ± 3 ppm) was added. At 6h40, when the temperature was 103.6 °C, a dose of Pt catalyst in IPA (5000 ppm active level) (0.021 g / ± 3 ppm) was added. At 7h13, when the temperature was 103.4 °C, the reaction was stopped and another H+NMR was taken. This second NMR analysis confirmed that there was no more SiH reacting. A total of 21.49 ppm of catalyst was used.
[0077] In this example 19, SPE copolymer sample 19 was prepared as follows: the hydrosilylation reaction was carried out in a 250 mL four necked round bottom flask, equipped with a mechanical overhead stirrer, a thermocouple, a stopper, a condenser and a nitrogen inlet. The heating system was through a heating mantle with a PT-100 temperature controller. A-6) PPh methallyl ether (2.5 g, 1stpart, 6.5%) and 17.51 g of M2D 21.4 D H 50The mixture was heated to 100 °C under nitrogen. After 18 minutes, when the temperature reached 100.5 °C, a Pt catalyst in IPA (5000 ppm active level) was added at ± 6 ppm. This reaction was exothermic and the temperature rose to 115.2 °C at 19 minutes. At 35 minutes, when the temperature reached 100.4 °C, the 2nd portion of A-6) PPh methallyl ether (5.6 g) was added dropwise through the funnel over 5 minutes. At 41 minutes, when the temperature was 100 °C, a second dose of Pt catalyst in IPA (0.035 g / ± 3 ppm) was added. At 42 minutes, the temperature reached 102.5 °C. At 60 minutes, when the temperature reached 100.2 °C, the 3rd portion of A-6) PPh methallyl ether (10.06 g) was added dropwise through the funnel over 3 minutes. At 2h27, when the temperature reached 101.2 °C, the 4th portion of A-6) PPh methallyl ether (6.03 g) was added dropwise through the funnel over 4 minutes. At 3h13, when the temperature reached 100.8 °C, the 5th portion of A-6) PPh methallyl ether (5.61 g) was added dropwise through the funnel over 2 minutes. At 4h00, when the temperature reached 99.5 °C, the last portion of A-6) PPh methallyl ether (8.47 g) was added dropwise through the funnel over 2 minutes. At 4h22, when the temperature was 100 °C, a third dose of Pt catalyst in IPA (5000 ppm active level) was added (0.065 g / ± 6 ppm). At 5h45 and with a temperature of 100.2 °C, the reaction was stopped and an H+NMR was performed to see if there were still SiHs unreacted. The next day (15.09.2022), the reaction was restarted and at 54 minutes, when the temperature reached 100 °C, a Pt catalyst in IPA (5000 ppm active level) was added at ± 6 ppm. At 1h40, when the temperature was 99 °C, a dose of Pt catalyst in IPA (5000 ppm active level) was added (0.032 g / ± 3 ppm). At 4h12, when the temperature was 100.5 °C, a dose of IPA (0.842 g) was added to increase the compatibility between the methallyl and SiH. At 5h14, when the temperature was 102.5 °C, a dose of Pt catalyst in IPA (5000 ppm active level) was added (0.055 g / ± 5 ppm) - at 5h16 the temperature increased to 103.6. At 6h20, when the temperature was 100 °C, the reaction was stopped and another H+NMR was performed. This second NMR analysis confirmed that there were no more SiHs reacted. A total of 27.46 ppm of catalyst was used.
[0078] In this example 20, SPE copolymer sample 20 was prepared as follows: The hydrosilylation reaction was carried out in a 250 mL four necked round bottom flask, equipped with a mechanical overhead stirrer, a thermocouple, a stopper, a condenser and a nitrogen inlet. The heating system was through a heating mantle with a PT-100 temperature controller. A-6) PPh methallyl ether (4.48 g, 1st portion, 13.5%) and 25.65 g of M2D 57.5 D H 44 M. The mixture was heated to 100°C under nitrogen. After 31 minutes, when the temperature reached 97°C, a Pt catalyst at ± 5 ppm in IPA (5000 ppm active level) was added. No exotherm was observed in this example. At 44 minutes, when the temperature was 99.5°C, 0.34 g of IPA was added to increase the compatibility between the methallyl and SiH groups. When the temperature controller was set at 102°C, an exotherm was observed at 52 minutes (105.3°C). At 1 h 03, when the temperature reached 98.6°C, the 2nd portion of A-6) PPh methallyl ether (5.99 g) was added dropwise through the funnel during 2 minutes. At 1 h 29, when the temperature was 100°C, a second dose of Pt catalyst (0.072 g / ± 5 ppm) in IPA (5000 ppm active level) was added. At 1 h 35, when the temperature reached 100.6°C, the 3rd portion of A-6) PPh methallyl ether (11.08 g) was added dropwise through the funnel during 3 minutes. At 3 h 42, when the temperature was 101°C, a third dose of Pt catalyst (0.071 g / ± 5 ppm) in IPA (5000 ppm active level) was added. At 3 h 46, when the temperature reached 101.2°C, the last portion of A-6) PPh methallyl ether (11.54 g) was added dropwise through the funnel during 6 minutes. At 4 h 27, when the temperature was 101.5°C, a fourth dose of Pt catalyst (0.159 g / ± 13 ppm) in IPA (5000 ppm active level) was added - the temperature reached 102.4°C at 4 h 29. At 6 h 19 and temperature 99.7°C, the reaction was stopped and H+NMR was performed to see if there was still SiH unreacted. This NMR analysis confirmed that there was no more SiH to react. A total of 24.51 ppm of catalyst was used.
[0079] In this example 21, SPE copolymer sample 21 was prepared by repeating example 17.
[0080]
[0081] In this suds control example A, the SPE copolymers and comparative copolymers prepared as described above were evaluated for suds control performance with silicone resin and silica, or without silicone resin and silica (neat) using the Quick Suds Test for suds control performance. The Quick Suds Test for suds control performance was performed as follows: 300 mL of water with a defined water hardness (23° French hardness) was added to a rotating tube. The neat copolymer or 0.7 g of a detergent formulation containing the copolymer in Table D as a suds suppressor candidate was added. The tube was rotated at 30 RPM for 9 minutes. The foam height (cm) was then measured. In the absence of a suds suppressor candidate, the tube was full of foam (24 cm) at the end of the 9 minute rotation. The amount of copolymer added was 0.1% or 0.5%, and the results of the Quick Suds Test are shown in Tables 4 and 5 below.
[0082]
[0083]
[0084] The data in Table 4 shows that all of the neat SPE copolymers tested exhibited better suds control characteristics than the control (copolymer of Example 7, which has pendant groups derived from alpha methyl styrene but does not have pendant groups derived from an allyloxy-terminated, phenyl-terminated glycol ether). The SPE copolymers of the present invention provide the unexpected benefit of providing good suds control characteristics in the absence of an MQ resin and silica, which can make these SPE copolymers suitable for simpler suds control formulations than those currently commercially available that contain silicone resin and hydrophobic filler. Surprisingly, the SPE copolymers with silicon-bonded pendant groups derived from an allyloxy-terminated, phenyl-terminated glycol ether but not containing pendant groups derived from alpha methyl styrene (i.e., the SPE copolymers of Example 10, Example 11, Example 14, and Example 15) exhibited better suds control characteristics than the SPE copolymers containing pendant groups derived from alpha methyl styrene and an allyloxy-terminated, phenyl-terminated glycol ether (i.e., the SPE copolymers of Example 8, Example 9, and Example 16) under the conditions of this example test, particularly at 0.5% loading.
[0085] In this Foam Control Formulation Example I (FCF I), Foam Control Formulation samples were prepared as follows: In a 20 mL plastic container suitable for a Hauschild Speed Mixer, 8.7 g of the SPE copolymer (or comparative copolymer) synthesized as described above, 0.7 g of MQ resin, and 0.6 g of Sipernat D10-1 were weighed. The resulting blend was first mixed at 3500 RPM for 30 seconds. The plastic container was opened and inspected to check for potential silica agglomerates. If silica agglomerates needed to be broken up, a second mixing at 3500 RPM for 30 seconds was applied. Certain Foam Control Formulations prepared as described in this example were evaluated using the Quick Foam Test described below. The results are shown in Table 5 below.
[0086]
[0087] The data in Table 5 shows that all of the tested SPE copolymers provided good foam control in conventional Foam Control Formulations containing silicone resin and silica filler under the conditions tested. Certain of the SPE copolymers improved the foam control performance relative to the comparative examples. The SPE copolymers of Examples 17-21 improved the foam control performance (relative to the comparative copolymers) under the conditions tested in this example, even though the SPE copolymers of Examples 17-21 did not contain any pendant groups derived from alpha methyl styrene.
[0088] In this Foam Control Formulation Example II, the Foam Control Formulations prepared in Foam Control Formulation Example I were evaluated using the Washing Machine Foam Control Procedure described below. The results are shown in Tables 6, 7, and 8 below.
[0089]
[0090] The data in Table 6 shows that the SPE copolymers having silicon-bonded pendant groups derived from alpha methyl styrene and alkenyloxy-terminated, phenyl-terminated glycol ether provided good foam control performance in the Foam Control Formulations tested. Sample FCF I-9, in which the SPE copolymer of Example 9 was used, and which contained silicon-bonded pendant groups derived from A-6) PPh methylallyl ether, showed improved foam control performance compared to the control, which had silicon-bonded pendant groups derived from alpha-methyl styrene, but did not have silicon-bonded pendant groups derived from alkenyloxy-terminated, phenyl-terminated glycol ether.
[0091]
[0092] The data in Table 7 shows that the SPE copolymer with pendant silicon-bonded groups derived from an enoxy-terminated, phenyl-terminated glycol ether (but not from alpha methyl styrene) provided some suds control performance under the conditions tested in this example, although it was not as good as the SPE copolymer containing pendant silicon-bonded groups derived from alpha methyl styrene and an enoxy-terminated, phenyl-terminated glycol ether (shown in Table 6 above) under the conditions tested in this example.
[0093]
[0094] The data in Table 8 shows that the suds control formulation containing the SPE copolymer with 2 equivalents of pendant groups derived from an enoxy-terminated, phenyl-terminated glycol ether and 31 equivalents of pendant groups derived from alpha methyl styrene provided the best antifoam performance under the conditions tested. The suds control performance of this sample, FCF I - 9, was better than the comparative example in which the copolymer had pendant groups derived from alpha methyl styrene but not from an enoxy-terminated, phenyl-terminated glycol ether. The other samples tested did show some suds control performance.
[0095] In this suds control formulation example III, the SPE copolymer prepared in Example 10 was formulated into suds control formulations containing different silicone resins. The samples were prepared as described in suds control formulation example I, but using the SPE copolymer of Example 10 and the silicone resins shown in Table 9 below.
[0096]
[0097] The laundry machine antifoam procedure described below was completed on the samples in Table 9. Good antifoam performance was obtained using all of the MQ resins tested. When all other starting materials were the same under the conditions tested in this example, it was found that MQ resin (III) provided better antifoam performance than MQ resin (IV). No significant difference was observed between MQ resin (I) and MQ resin (II) under the conditions tested.
[0098] In this suds control formulation example IV, the SPE copolymers of Examples 10 and 17-20 were formulated into suds control formulations using the procedure in suds control formulation example I, except that the SPE copolymer selected was changed. The suds control formulations were evaluated in the laundry machine antifoam procedure described below. The results are in Table 10.
[0099]
[0100] The examples in Table 10 show that the use of a SPE copolymer without silicon-bonded pendant groups derived from alpha methyl styrene provided some suds control performance under the conditions tested in this example.
[0101] Rapid foaming test for sudsing performance
[0102] Add 300 mL of water with a defined water hardness (23° French hardness) to a rotating tube. Add 0.7 g of a detergent formulation containing the copolymer in Table D as an antifoam candidate. Rotate the tube at 30 RPM for 9 minutes. Then measure the foam height (cm). In the absence of an antifoam candidate, the tube is filled with foam at the end of the 9 minute rotation (24 cm).
[0103]
[0104] Washing machine sudsing program :
[0105] In a Miele W1914 containing 11 clean thick terry towels (dry weight of 2 Kg) or 16 clean thick terry towels (3.5 Kg), 50 g of the detergent formulation described above in Table D with 0.1 wt% antifoam is added with 15 liters of soft water unless otherwise noted. The hardness of the wash liquor is manually adjusted by adding 5 mL of a calcium ion solution (262 g of CaCl2.2H2O / liter) and 19 mL of a magnesium ion solution (72 g MgCl2 / liter). The 40 °C cotton program is used with the spin speed set at 1400 rpm. The foam height in the front window is monitored every five minutes throughout the wash cycle. This test is followed by 2 additional laundry wash cycles (temperature set at 95 °C then at 40 °C) to remove any antifoam residue and to avoid detergent build-up.
[0106] Industrial applicability
[0107] The above examples demonstrate that the silicone-polyether copolymers described herein can be used as a foam control agent. The copolymers can be used neat (e.g., without an MQ resin and / or silica in the foam control formulation) and provide good foam control as demonstrated in Foam Control Example A. Certain copolymers (e.g., copolymers having silicon-bonded pendent groups derived from allyloxy-terminated, phenyl-terminated glycol ethers but not containing pendent groups derived from alpha methyl styrene) can provide better foam control when used neat than those copolymers having both silicon-bonded pendent groups derived from allyloxy-terminated, phenyl-terminated glycol ethers and silicon-bonded pendent groups derived from alpha methyl styrene as shown in Table 4. Other copolymers (e.g., copolymers having silicon-bonded pendent groups derived from allyloxy-terminated, phenyl-terminated glycol ethers and silicon-bonded pendent groups derived from alpha methyl styrene) can provide better foam control performance when formulated in a foam control formulation containing a filler (e.g., silica) and a silicone resin (e.g., an MQ resin) as shown in Tables 5 and 7. Without wishing to be bound by theory, it is believed that the copolymers of the present invention can be made by selecting starting materials to provide copolymers that provide good foam control for a variety of different applications such as foam control formulations and / or detergent compositions.
[0108] Definitions and usage of terms
[0109] All amounts, ratios, and percentages herein are by weight unless otherwise indicated by the context of the specification. The articles 'a', 'an', and 'the' each refer to one or more, unless otherwise indicated by the context of the specification. The singular forms also include the plural unless otherwise indicated by the context of the specification. The summary and abstract herein are hereby incorporated by reference. The amounts of all starting materials in the compositions total 100%. The transitional phrases “comprising”, “consisting essentially of”, and “consisting of” are used according to the Ninth Edition of the Patent Examining Procedure, Revised as of January 2018, Revision 08.2017, Chapters §2111.03 I., II., and III. Any feature or aspect of the present invention can be used in combination with any other feature or aspect described herein. Abbreviations used herein have the definitions in Table 11.
[0110]
Claims
1. A silicone-polyether copolymer having the following unit formula: wherein the subscripts a, b, and c represent the average number of each unit in the unit formula and have values such that b = 20 to 60; c = 20 to 50; each R is independently selected from the group consisting of H, a halogen atom, OH, methyl, and methoxy; D' is a covalent bond, a group of the formula -CH2-, or a group of the formula -CH2-O-; and R" is H or methyl; and X is H or methyl, D has an empirical formula of -C2H4- or -C3H6-, and the subscript n is 1, 2, or 3. (R 1 3SiO 1 / 2 ) a (R 1 2SiO 2 / 2 ) b (R 1 R 2 SiO 2 / 2 ) c wherein 2. The copolymer of claim 1, wherein D is selected from -CH2-CH2- or -CH2-CH(CH3)-, and X is as described above. a = 2; 7. Use of the copolymer of any one of claims 1 to 6 as a suds control agent.
8. A suds control formulation comprising: A) the copolymer of claim 3 or claim 4; B) a hydrophobic filler in an amount of 0.5 wt% to 50 wt% based on the weight of the copolymer of A), C) a silicone resin in an amount of 1 wt% to 50 wt% based on the weight of the copolymer of A), and D) an organic solvent in which the silicone resin is soluble in an amount of 0 wt% to 60 wt% based on the weight of the silicone resin of C). each R is an alkyl group of from 1 to 12 carbon atoms independently selected; and 1 each R is an alkyl group of from 1 to 12 carbon atoms independently selected; and each R is independently selected from the group consisting of H, formula (E1'), formula (D1'), and formula (A1'), wherein 2 is independently selected from the group consisting of H, formula (E1'), formula (D1'), and formula (A1'), wherein Formula E1') is wherein R 1 As described above, subscript m is 0 or 1, and each R 6 is a divalent hydrocarbon group; Formula D1') is wherein 9. The suds control formulation of claim 8, further comprising an additional starting material selected from the group consisting of a water-dispersible carrier, a water-miscible liquid, an adhesive, a sealant, a cyclic siloxane, a thickener, water, a surfactant, a preservative, a water-insoluble organic compound, and a combination of two or more thereof.
10. A suds control formulation, wherein the suds control formulation is an emulsion comprising a dispersed phase comprising the copolymer of any one of claims 1 to 6 in an amount of 5 wt% to 80 wt% based on the weight of the emulsion, a continuous phase comprising water, a surfactant, and optionally, an additive selected from the group consisting of a preservative, a viscosity modifier, a protective colloid, and a thickener.
11. A laundry detergent composition comprising: i) the copolymer of any one of claims 1 to 6 or the suds control formulation of any one of claims 8 to 10, and ii) a detersive surfactant. Formula A1') is ; wherein 12. The laundry detergent composition of claim 11, further comprising an additional starting material selected from the group consisting of an anti-redeposition agent, a brightener, a chelant, an enzyme, a bacteriostat, a solvent, a pH adjuster, an opacifier, a perfume, a dye, a color stabilizer, a bactericide, a soil release agent, a softening agent, a soap, a carrier, a builder, a structurant, an adjuvant, a hydrotrope, a dispersant, a rheology modifier, and a combination of two or more thereof.
13. The laundry detergent composition of claim 12, wherein the laundry detergent composition is a liquid laundry detergent composition. provided that at least one instance of R 2 has the formula A1'). Each R 1 It is methyl. Formula D1') is and Formula A1') is wherein 3. The copolymer of claim 2, wherein X is methyl, D is -CH2-CH(CH3)-, and > 50 mol% of R per molecule 2 All examples of Formula D1) have the formula D1').
4. The copolymer of claim 3, wherein 93 to 95 mole percent of R 2 has formula D1') and 5 to 7 mole percent of R 2 has formula A1').
5. The copolymer of claim 1 or claim 2, wherein R 2 each instance of A1) has the formula A1').
6. The copolymer according to any one of claims 1 to 5, wherein formula A1') is selected from the group consisting of: , , and . 14. The laundry detergent composition of any one of claims 11-13, wherein i) the copolymer or the suds-controlling formulation is present in an amount of from 0.001 wt.% to 5 wt.%, based on the weight of the laundry detergent composition.
Citation Information
Patent Citations
Organic silicon composition, and preparation and use thereof
EP3210663A1
Defoaming agent for liquid detergent
US10407647B2
Plant extract for skin infections
US11318182B1
Linear silicone polyether foam control agent
US11383182B2
Defoamer compositions
US20090137446A1